Sobre o lugar do “índio” : a expansão da UFAL, Campus do Sertão, e seus efeitos na formação superior de povos indígenas (2010-2020) - Nascimento, Ayrton Matheus da Silva (2022)
The presence of Indigenous Peoples in the University is a relatively new phenomenon compare to the long, established and elitist history of Brazilian University. This scene was gradually being changed by the policies of democratization of education, the social movements and the adoption of public policies of affirmative action to encourage social minorities to entry and permanence in public Colleges in the Brazilian context. In this study, from the public policies of expanding the Universities to small towns that started in Lula’s presidential government (2007), and the expansion and restructuring program (REUNI), was investigated the formation and access to higher education of Indigenous groups and the impacts/reflexes produced by their entry into this type of education in the period between the years 2010-2020, having as an investigative locus the higher “Sertão” of Alagoas, at the Federal University of Alagoas, Sertão’s Campus, with the objective to perceive the protagonism and the insertion of indigenous people in higher education. Concerning the theoretical-methodological aspects that guided our research, and as a result of the COVID-19 pandemic, we opted for a qualitative approach, in which we seek to mobilize the tools of Oral History, through the use of semistructured interviews, with former Indigenous students. The techniques of analysis can be configured by the use of Content Analysis, allowing us to perceive how the presence of those people have provoked significant (re)designs in terms of their trajectories of life, from their insertions in academic-university spaces and their respective communities.